2015
DOI: 10.3174/ajnr.a4493
|View full text |Cite
|
Sign up to set email alerts
|

Improved Brain Tumor Classification by Sodium MR Imaging: Prediction ofIDHMutation Status and Tumor Progression

Abstract: BACKGROUND AND PURPOSE: MR imaging in neuro-oncology is challenging due to inherent ambiguities in proton signal behavior. Sodium-MR imaging may substantially contribute to the characterization of tumors because it reflects the functional status of the sodium-potassium pump and sodium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 47 publications
1
58
0
Order By: Relevance
“…Previous authors have demonstrated increased TSC within CNS neoplasms such as high-grade glioma, 17,32,39 and that 23 Na MRI can be used as a predictive marker of both tumor grade 32 and prognosis. 17 Within glioma, cellular proliferation and changes in cell membrane ion transporters 17 contribute to elevated intracellular sodium concentrations, but these tumors also display increases in the sodium-rich extravascular-extracellular space secondary to necrosis and loss of normal cellular packing. [10][11][12][13][14] Evidence from in vivo animal studies of temporal 23 Na MRI changes in glioma following chemotherapy treatment suggest that TSC may also serve as an early marker of progression and treatment response in this tumor group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have demonstrated increased TSC within CNS neoplasms such as high-grade glioma, 17,32,39 and that 23 Na MRI can be used as a predictive marker of both tumor grade 32 and prognosis. 17 Within glioma, cellular proliferation and changes in cell membrane ion transporters 17 contribute to elevated intracellular sodium concentrations, but these tumors also display increases in the sodium-rich extravascular-extracellular space secondary to necrosis and loss of normal cellular packing. [10][11][12][13][14] Evidence from in vivo animal studies of temporal 23 Na MRI changes in glioma following chemotherapy treatment suggest that TSC may also serve as an early marker of progression and treatment response in this tumor group.…”
Section: Discussionmentioning
confidence: 99%
“…23 Na MRI has been shown to be sensitive to therapy‐induced changes in both breast and central nervous system tumors . In a recent study, 23 Na MRI outperformed an invasive histological correlate for brain tumor prognostication . 23 Na MRI may therefore allow better assessment of tissue cellularity and may allow treatment to be more personalized as a result of documenting the variety of responses seen within and between tumors.…”
mentioning
confidence: 99%
“…In recent years, researchers have evaluated the feasibility of applying several MRI techniques to determine IDH status in patients with gliomas (14)(15)(16)(17)(18), including gadoliniumenhanced T 1 -weighted (Gd-T 1 w) images (19), diffusion (20)(21)(22), perfusion (23), sodium MRI (24), and machinelearning algorithms (25,26). Notably, because lab studies have proven that the oncometabolite 2-hydroxyglutarate (2-HG) holds a 100-fold increase in IDH-mutant cells compared to IDH-wildtype type cells (27), recent studies also have shown that significantly higher 2-HG detected by single-voxel MRS can identify patients with IDH1-mutant gliomas with high sensitivity (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…SODIUM MAGNETIC RESONANCE (MR) techniques provide valuable information about cell physiology and viability and could be useful as a biomarker in vivo . Tissue sodium levels increase in multiple conditions, such as in stroke, multiple sclerosis, and radiotherapy treatment monitoring . Sodium levels increase within cells, if the sodium‐potassium pump cannot maintain the gradient of intracellular and extracellular sodium by pumping three sodium ions from intracellular space to the extracellular space with two potassium ions being exchanged against the electrochemical gradient (Na int ˜15 mM, Na ext ˜140 mM).…”
mentioning
confidence: 99%